Pelaksanaan Sistem dan Prosedur Administrasi Perceraian di Kabupaten Pelalawan - Pebrina, Reni (JURNAL RISET INOVASI DAERAH, 2023)
This paper discusses the implementation of divorce administration systems and procedures in Pelalawan Regency, focusing on civil servants (PNS) working for the government. The study aims to explore the reasons for divorce among civil servants and analyze the current procedure for obtaining divorce permits. The study was based on government regulations on divorce for civil servants, which required permission from authorized officials. The study found that there are still some shortcomings in the current administrative procedures for divorce in Pelalawan District, which are done manually. The research suggests that there is a need for better education and understanding of divorce procedures among civil servants. Research methods are important in obtaining data for specific purposes. The research was conducted in the Pelalawan District Government with six informants, including the Head of BKPSDM, Inspector, and teachers. Data was collected through interviews and documentation. The analysis used is qualitative descriptive. The study found that divorce is a complex issue, and the reasons for divorce among civil servants are often caused by ongoing conflicts and disputes. The government has regulations to make divorce difficult for civil servants, but mediation and counseling can help prevent divorce. The divorce process can have a negative effect on children, and it is important to address the factors that lead to divorce.